Histological assessment of the local effect of different concentrations of aminoguanidine hydrochloride on bone healing in rats - Ali Reza Farhad; Fahimeh Razavi; Sayed Mohammad Razavi; Masoud Saatchi; Maziar Manshaei (Wolters Kluwer Medknow Publications, 2021)
Background: Nitric oxide (NO) has several functions in bone healing and affects bone metabolism. Selective inducible NO synthase (iNOS) inhibitors can be used to assess the efficacy of NO for healing of bone defects. This study sought to assess the local effect of different concentrations of aminoguanidine hydrochloride (AG), a selective iNOS inhibitor, on bone healing in rats. Materials and Methods: In this animal experimental study, 72 rats were divided into six groups of control, placebo, 5% AG, 10% AG, 15% AG, and 20% AG. A bone defect measuring 5 mm × 5 mm was created in the femur. The defect remained empty in the control group. In the placebo group, neutral gel was placed in the bone defect, and in the remaining four AG groups, different concentrations of AG were applied to the defects. Bone healing was assessed histologically. The healing score in the six groups was analyzed by the Kruskal-Wallis test. A P < 0.05 was considered statistically significant. Results: The healing score in 20%, 15%, 10%, and 5% AG groups was significantly higher than that in the neutral gel and control groups (P < 0.01). Among the four groups of AG, 20% concentration showed better results, but the difference was not significant. Conclusion: Four concentrations of AG caused greater bone healing compared to the other two groups. Selective iNOS inhibitors such as AG can be used to promote local bone healing.